Result of Total Hip Replacement (THR) in Arthritis of Hip at DMCH) in the Year 2017 - Hossain, Md Mobarak; Alam, Quazi Shahidul; Parvej, Masud; Rahman, Md Ashfaqur; Hossain, Akhter; Saha, Haridas (Journal of Dhaka Medical College, 2018)
Introduction: In arthritic condition like osteoarthritis or rheumatoidarthritis, the hip joint becomes very much painful. Patient can hardly walk or even stand up in advance condition. But total hip replacement can give them new hope to live(1). Medication can relieve the symptom variably but THR can be the ultimate solution for these type of patients. Materials & Methods: We have operated total sevenpatients in the year, 2017 at DMCH. All have painful hip with advance stages of arthritis. Both cemented and non-cemented THR done for them according to their clinical condition. Early mobilization with the help of walker started for them as soon as the pain permits. Results: Results were evaluated by Harris Hip Score. All the patients were found clinically improved. Outcome measured with Harris Hip Score was excellent in 4 cases, good in 2 cases and fair in 1 case. Conclusion: THR is now a days a gold standard of practice throughout the world with published journal. We have started this practice in Bangladesh too and this time at DMCH in a large scale. Results are yet to be decided as at least 1 year follow up is required to find out how they do in our local community. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 14-16